Remote work demands and work-life balance: Moderating effect of perceived leadership behavior - Arthi, R; Gita, P C (Journal of Asian Scientific Research, 2024)
This study investigates the relationship between remote work demands, work stress, and work-life balance among employees in the service sector, specifically those working in Information Technology companies. The COVID-19 pandemic has forced organizations to shift to a new mode of working, which has led to significant changes in work and family roles. Due to the unpredicted changes, remote work causes work stress among employees. A cross-sectional study was chosen, and data were gathered from 242 employees working in the service industry. A purposeful sampling technique is used, and data were collected using a questionnaire. Grounded with Conservation of Resources (COR) stress theory and transformational leadership theory, the result of moderated mediation analyses specifies that the negative influence of remote work demands on the work-life balance of employees is potentially increased by work stress and reversed by the influence of their leader’s behavior style, specifically transformational leadership. Through the dimensions of transformational leadership such as idealized influence, inspirational motivation, individualized consideration, intellectual simulation, the leaders help the individuals working in the team cope with stress and support them in all possible ways to achieve the goal. The outcome also signifies the moderating effect of gender on balancing work and life.